Nursing with a Message : Public Health Demonstration Projects in New York City - D'Antonio, Patricia, 1955- (Book collections on Project MUSE., 2017)
"Mandated by the Affordable Care Act, public health demonstration projects have been touted as an innovative solution to the nation's health care crisis. Yet, such projects actually have a long but little-known history, dating back to the 1920s. This groundbreaking new book reveals the key role that these local health programs--and the nurses who ran them--influenced how Americans perceived both their personal health choices and the well-being of their communities.Nursing with a Message transports readers to New York City in the 1920s and 1930s, charting the rise and fall of two community health centers, in the neighborhoods of East Harlem and Bellevue-Yorkville. Award-winning historian Patricia D'Antonio examines the day-to-day operations of these clinics, as well as the community outreach work done by nurses who visited schools, churches, and homes encouraging neighborhood residents to adopt healthier lifestyles, engage with preventive physical exams, and see to the health of their preschool children. As she reveals, these programs relied upon an often-contentious and fragile alliance between various healthcare providers, educators, social workers, and funding agencies, both public and private. Assessing both the successes and failures of these public health demonstration projects, D'Antonio also traces their legacy in shaping both the best and worst elements of today's primary care system"--